2023
DOI: 10.3390/biomedicines11071971
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Peptide-Based Delivery of Macromolecular Drugs: Development, Strategies, and Progress

Abstract: Cell-penetrating peptides (CPPs), developed for more than 30 years, are still being extensively studied due to their excellent delivery performance. Compared with other delivery vehicles, CPPs hold promise for delivering different types of drugs. Here, we review the development process of CPPs and summarize the composition and classification of the CPP-based delivery systems, cellular uptake mechanisms, influencing factors, and biological barriers. We also summarize the optimization routes of CPP-based macromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 215 publications
0
11
0
1
Order By: Relevance
“…Nanoparticles exceeding 6 nm in diameter are often processed by the liver and spleen, while those smaller than 6 nm are processed by the kidneys [ 58 ]. In addition, if nanoparticles are smaller than 10 nm, they are quickly cleared by the kidneys and do not easily accumulate at the tumor site through EPR effect [ 60 ]. In our study, M—WIP2W, approximately 20 nm in size, showed promise with regard to efficient distribution in the body.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles exceeding 6 nm in diameter are often processed by the liver and spleen, while those smaller than 6 nm are processed by the kidneys [ 58 ]. In addition, if nanoparticles are smaller than 10 nm, they are quickly cleared by the kidneys and do not easily accumulate at the tumor site through EPR effect [ 60 ]. In our study, M—WIP2W, approximately 20 nm in size, showed promise with regard to efficient distribution in the body.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, most short CPPs are recognized by their positive charge, allowing them to traverse the cell membrane at relatively low concentrations. Although several clinical trials involving conjugated CPPs are ongoing, no CPP-based drug has been approved 40 , 41 . Consequently, the discovery and design of novel CPPs with improved efficiency, specificity, and safety profiles remain highly desirable in biomedical research.…”
Section: Discussionmentioning
confidence: 99%
“…119 An additional justification for these mutations was based on ample evidence that uptake and endosomal escape are heavily dependent on the presence of numerous positively charged residues, such as lysine and arginine. [120][121][122][123][124][125] Independent staining of endosomes and crystals revealed that while cellular uptake occurred for both versions of Cry3Aa, endosomal escape into the cytoplasm was only observed for Pos3Aa crystals. Using different endocytic inhibitors, it was further observed that uptake was not receptor mediated, but instead occurred via macropinocytosis.…”
Section: Therapeutic Deliverymentioning
confidence: 99%